가미의이인탕이 통풍유발 흰쥐에 미치는 영향 - 엄현섭(Hyun Sup Eom) (동의생리병리학회지, 2007)
In order to obtain practical application of Yiyiren-tang against gout disease, water extract of modified Gami-Yiyiren-tang(GYYT) added with Lonicera japonica is prepared through decoction and freeze drying. The effects were evaluated with blood sample from ICR mice treated with MSU intra-peritoneal injection 1 time a day, 3 days consecutively. The results were as follows. GYYT decreased C-reactive protein level and HDL cholesterol levels. But the creatinine, the LDL cholesterol levels, triglyceride and uric acid levels were not changed were decreased significantly. These results show that GYYT can be used effectively against the urate-related gout disease. But not better than effects of the Gami-daehwangmokdan-tang. KCI Citation Count: 0